2002
DOI: 10.1364/ao.41.002724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiance and polarization values observed in the Mediterranean Sea and simulated in a Monte Carlo model

Abstract: Measurements of the radiance and degree of polarization made in 1971 in the Mediterranean Sea are presented along with the simulation of all observed quantities by a Monte Carlo technique. It is shown that our independent scattering treatment utilizing a Stokes vector formalism to describe the polarization state of the light field produces remarkably good agreement with those values measured in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…An analytic description of the radiance distributions has been suggested by Aas and Højerslev (1999). It supports the quality of the measurements so that when the in situ values were compared to radiances and polarizations simulated in a Monte Carlo model by Adams et al (2002), a remarkably good agreement was observed. Another agreement was found for Q as a function of the solar angle in a comparison between the simulations of Morel and Gentili (1996) and our Mediterranean measurements Højerslev 1999, Morel et al 2002).…”
Section: Datasets Of Field Measurementsmentioning
confidence: 55%
“…An analytic description of the radiance distributions has been suggested by Aas and Højerslev (1999). It supports the quality of the measurements so that when the in situ values were compared to radiances and polarizations simulated in a Monte Carlo model by Adams et al (2002), a remarkably good agreement was observed. Another agreement was found for Q as a function of the solar angle in a comparison between the simulations of Morel and Gentili (1996) and our Mediterranean measurements Højerslev 1999, Morel et al 2002).…”
Section: Datasets Of Field Measurementsmentioning
confidence: 55%
“…The data were stored as graphs on paper rolls from printers. Through the years the recordings were read off and tabulated (Lundgren 1971;, and analyses were made Aas and Højerslev, 1999;Adams et al, 2002 ).…”
Section: Observations Of Sub-surface Radiance and Irradiancementioning
confidence: 99%
“…Unfortunately only two theoretical works using this program were created by its author [1,2]. And another only one work [3], comparing the results of the Monte Carlo code containing the polarization and the measured data was published so far. It seemed expedient to create the second independent program of its kind in the world, specifically targeted to study phenomena related to surface of the sea.…”
Section: Introductionmentioning
confidence: 99%